Evaluation of Infiltration Models with Double Ring Infiltrometer Test on Residual Soil in Kulonprogo, Indonesia - Muntohar, Agus Setyo; Ikhsan, Jazaul; Setiati, Rehni; Uzuoka, Ryosuke (Civil Engineering Dimension, 2025)
The hydraulic conductivity of soil is an essential parameter for evaluating the slope instability triggered by rain infiltration. This research uses a Double-Ring Infiltrometer (DRI) at five locations to estimate the hydraulic conductivity from a field infiltration test. Four infiltration models were examined to estimate hydraulic conductivity, including Green–Ampt, Kostiakov, Horton, and Philips equations. Curve fitting on the infiltration rate–time plots were computed with the least square error to determine the infiltration parameters using Levenberg–Marquardt algorithm. The basic infiltration rate ranges from 6.88 mm/h to 721.5 8 mm/h.  The Horton and Philips infiltration model provides better statistical performance to estimate the infiltration rate. The estimated hydraulic conductivity from the four infiltration models results in a relative convergence value; however, the estimation results in more biased hydraulic conductivity at locations containing clay fraction and high-plasticity silt, especially for Green–Ampt and Philip infiltration models.